2022
DOI: 10.1093/oncolo/oyac189
|View full text |Cite
|
Sign up to set email alerts
|

Profile and Predictors of Blood Tumor Mutational Burden in Advanced Hepatocellular Carcinoma

Abstract: Advanced hepatocellular carcinoma (HCC) is responsive to immune checkpoint inhibitors, but there are currently no known biomarkers to predict treatment benefit. Blood TMB (bTMB) estimation via circulating tumor DNA (ctDNA) profiling can provide a convenient means to estimate HCC TMB. Here we provide the first landscape of bTMB in advanced HCC using a commercially available next-generation sequencing assay, show that it is approximately three times as high as matched tissue TMB, and show that bTMB correlates wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 11 publications
1
4
0
Order By: Relevance
“…They performed ctDNA profiling using commercially available NGS assays in 136 patients with unresectable HCC from four cancer centers. In 28 patients, blood TMB (bTMB) levels were approximately three-fold higher than tissue TMB (tTMB) levels [167]. Qualitative analysis of somatic mutations in HCC-derived ctDNA has detected several oncogenes and tumor suppressor genes including RAS, TERT, TP53, PTEN, ARID2, and CTNNB1 that are consistent with the results of tissue analyses in 63% of cases [168,169].…”
Section: Circulating Tumor Dna and Circulating Tumor Cellssupporting
confidence: 65%
“…They performed ctDNA profiling using commercially available NGS assays in 136 patients with unresectable HCC from four cancer centers. In 28 patients, blood TMB (bTMB) levels were approximately three-fold higher than tissue TMB (tTMB) levels [167]. Qualitative analysis of somatic mutations in HCC-derived ctDNA has detected several oncogenes and tumor suppressor genes including RAS, TERT, TP53, PTEN, ARID2, and CTNNB1 that are consistent with the results of tissue analyses in 63% of cases [168,169].…”
Section: Circulating Tumor Dna and Circulating Tumor Cellssupporting
confidence: 65%
“…Specific microenvironments, e.g., inflammatory background, toxic mutagens and treatments, that could induce a characteristic mutational signature, provide a “selective pressure” driving HCC clonal evolution, and influence the accumulation of somatic mutations ( Figure 1 ). A similar study investigated the correlation between tissue TMB (tTMB) and blood TMB (bTMB), measured as ctDNA, in 136 patients with unresectable HCC enrolled by 4 centers, whose ctDNA profile was analyzed between October 2020 and July 2021 [ 31 ]. A high frequency of TP53, CTNNB1, and TERT mutations was observed in their ctDNA profiles.…”
Section: Tmb Analysis In Tumoral Specimenmentioning
confidence: 99%
“…This discrepancy is likely due to both technical factors, e.g., differences in sampling time, size and location of sequenced genome regions, or algorithms used for TMB calculation, and intrinsic biological mechanisms. In fact, ctDNA could derive from multiple tumor foci, each characterized by a peculiar mutational profile and evolution [ 31 ]. This study pointed out that the evaluation of bTMB and ctDNA, besides being reliable indicators of TMB in tumor tissue, may represent more representative markers of HCC evolution, since ctDNA can be derived from multiple tumor foci.…”
Section: Tmb Analysis In Tumoral Specimenmentioning
confidence: 99%
“…A study that enrolled 48 patients with aHCC indicated higher baseline ctDNA was correlated with higher TMB, while decreases in ctDNA levels after treatment were linked with longer PFS [ 86 ]. Franses et al also revealed a significant correlation between tissue TMB and blood TMB estimated by ctDNA [ 87 ]. In addition, a risk-scoring model based on cfDNA copy number variation (CNV) has been developed to forecast the clinical outcomes of hepatobiliary tumor patients receiving ICI therapy.…”
Section: Biomarkers Of Hepatocellular Carcinoma Immunotherapymentioning
confidence: 99%